2021
DOI: 10.1021/acsmaterialslett.1c00420
|View full text |Cite
|
Sign up to set email alerts
|

Benign Synthesis and Modification of a Zn–Azolate Metal–Organic Framework for Enhanced Ammonia Uptake and Catalytic Hydrolysis of an Organophosphorus Chemical

Abstract: The efficient uptake or catalytic degradation of toxic chemicals is needed to provide efficient protection for both individuals and the environment. Herein, we report the benign synthesis of a Zn–azolate metal–organic framework (MOF) known as MFU-4l using ethanol (EtOH) as a solvent, which is efficient in the hydrolysis of an organophosphorus chemical warfare simulant (dimethyl-4-nitrophenyl phosphate, DMNP). Impressively, EtOH-derived MFU-4l hydrolyzed DMNP with a half-life of 0.5 h using only 6 mol % catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…In aqueous solution, the organophosphorus moiety present in many warfare agents coordinates to the Zr node while homogeneous, outer-sphere bases hydrolyze the bound agent. The Zn-based MOF MFU-4l ,, and Ti-based MOF MUV-100 have also shown promise as catalysts for nerve agent degradation, with the Zn and Ti nodes demonstrating a similar role to that of Zr, the Lewis acidic active site in nerve-agent hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…In aqueous solution, the organophosphorus moiety present in many warfare agents coordinates to the Zr node while homogeneous, outer-sphere bases hydrolyze the bound agent. The Zn-based MOF MFU-4l ,, and Ti-based MOF MUV-100 have also shown promise as catalysts for nerve agent degradation, with the Zn and Ti nodes demonstrating a similar role to that of Zr, the Lewis acidic active site in nerve-agent hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…First explored in 2014 by Katz et al, UiO-66 showed promising activity for the hydrolysis and methanolysis of organophosphate (OP) compounds used as simulants for more toxic CWAs under humid or aqueous conditions . Since then, other Zr-based MOFs such as UiO-67, MOF-808, NU-1000, and others have been investigated for OP hydrolysis with similar mechanisms proposed for each structure. Previous studies have suggested increases in reactivity due to increased open metal sites (MOF-808) or increased diffusion (NU-1000), but benchmarking materials against UiO-66 is difficult due to different particle sizes and defect levels, which may play a significant role in reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs have been established as excellent platform materials in a variety of applications, including catalysis, , gas storage and separations, and chemical sensing, due to their high surface areas and ease of structural tunability. Importantly, excellent control over the pore environment has enabled selective uptake with high capacities for MOFs toward targeted analytes, including NH 3 and SO 2 . Among these materials, zirconium-based MOFs (Zr-MOFs) show great promise as they exhibit excellent chemical and thermal stability and a significant degree of topological diversity . For example, Zr-MOFs feature [Zr 6 (μ 3 -O) 4 (μ 3 -OH) 4 ] 12+ nodes that contain both Lewis acidic open metal sites and Brønsted acidic bridging and terminal hydroxo ligands that can engage in various modes of reactivity (Figure ), and varying the identity and geometry of the carboxylate linker offers access to many different network topologies.…”
Section: Introductionmentioning
confidence: 99%